Sitti Raihanun Zainuddin Abdul Madjid, Female Scholar of the 21st Century: Pioneer in Gender Transformation and Islamic Education in Lombok-West Nusa Tenggara - Lalu Gede Muhammad Zainuddin Astani; Ulyan Nasri; Fahrurrozi; Muhammad Thohri (Edukasia Islamika : Jurnal Pendidikan Islam, 2024)
This study investigates the pivotal role of Sitti Raihanun Zainuddin Abdul Majid as a 21st century female Islamic scholar who pioneered gender transformation and Islamic education in Lombok, West Nusa Tenggara. The research aims to uncover her influence in reshaping gender  roles through her leadership in Nahdlatul Wathan (NW) and her extensive contributions to  building educational institutions. Anchored in feminist theories, social transformation  frameworks, and female leadership paradigms, this study contextualizes her role in the broader  discourse on gender equality in Islamic education. Employing a qualitative descriptive method  with a hermeneutic approach, data were collected through in-depth interviews with NW  members, local community figures, and Sitti Raihanun herself, as well as analysis of  organizational documents and her public speeches. The findings reveal that her leadership was  shaped by a strong moral and religious upbringing, institutional charisma, and a strategic vision  to promote women’s leadership within Islamic contexts. Despite facing patriarchal resistance  and leadership controversies, she effectively implemented a transformative and charismatic  leadership model. Her efforts resulted in the establishment of hundreds of Islamic schools and  an expanded da'wah network across Indonesia. This study contributes to a nuanced  understanding of gender transformation in Islamic education and highlights the importance of  inclusive female leadership in advancing educational and societal change.